The role of cost accounting Systems in rationalizing public spending and achieving Budget Targets - Field Study:on Ministry of Finance, Economic and Manpower, White Nile State. Sudan - elnour karim eldinne omar, omar; Ibrahim Yusuf Ali, Zain Al-Abidin; Ali Abakar Mohamed, Hamid (Journal of Research in Finance and Accounting, 2026)
This study aims to show the role of cost accounting systems in rationalizing public spending and achieving budget targets. In roder to fulfill the requirements of the study, the study relied on the field method. The questionnaire was used as a means of collecting data. Statistical tools and methods were also used to analyze the data using the Statistical Package for Social Sciences (SPSS). The study found a number of results, Cost accounting systems help in investing money wisely, in good use of resources, and enhancing opportunities to provide basic services. Cost accounting systems provide useful information for budget preparation, execution and control.